Social Service Strategy in Improving Elderly Welfare: Evidence from Indonesia - Endah Ratnawaty Chotim (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The aims of this study were to find out the social service programs at the Pangudi Luhur Integrated Center in achieving elderly welfare, to find out the supporting and inhibiting factors of the social service strategy of the Pangudi Luhur Bekasi Integrated Center in achieving elderly welfare, and to find out the results achieved from these programs. the Pangudi Luhur Bekasi Integrated Center social service program for the elderly. This study uses a descriptive research method with a qualitative approach. The results of this study are that the condition of elderly clients has changed after receiving social services at the Pangudi Luhur Bekasi Integrated Center. Elderly clients have their needs fulfilled and grow independent so that they can carry out their social functions and can develop so that they can continue their old age productively. However, on the one hand, there has been a dysfunction in the social service strategy at the Pangudi Luhur Bekasi Integrated Center, namely based on the ADL assessment sample data above, there are elderly clients who experience mild to severe dependence. This is due to declining health conditions and declining physical function.